Attitudes of pregnant women and healthcare professionals to labour induction and obtaining consent for labour induction. (November 2021) - Coates, Rose
Abstract: Induction of labour is experienced by up to one third of women and can be a negative experience, in relation to both the decision about whether to have an induction of labour (IoL) and the experience of the process of IoL. This paper reviews the limited evidence of women's views on and experiences of: information provision; shared decision-making; preferences for method and location of IoL; indications for IoL; pain management; and effective communication and support. Healthcare professionals' views are reviewed, but are underrepresented, and further research is needed to understand experiences of gaining consent for IoL. Systematic review evidence is drawn on where possible, but reviews often found small numbers of papers for inclusion, and provide insights rather than conclusive evidence. Future research would benefit from using validated measures to assess the experience of IoL. Highlights: Measurement of induction of labour experience requires attention. Induction is a challenging experience for women. Information provision and shared decision-making are vital to a positive experience. Optimal care for women undergoing induction requires understanding of women's experiences. Research on clinicians' experiences of induction is needed.